Platinum(II) Iodido Complexes of 7-Azaindoles with Significant Antiproliferative Effects: An Old Story Revisited with Unexpected Outcomes - Štarha, Pavel; Vančo, Ján; Trávníček, Zdeněk; Hošek, Jan; Klusáková, Jarmila; Dvořák, Zdeněk (PLOS ONE, 2016)
A series of platinum(II) diiodido complexes containing 7-azaindole derivatives, having the general formula cis-[PtI2(naza)2] (1–8), has been prepared and thoroughly characterized, including X-ray structure analysis of cis-[PtI2(2Me4Claza)2]∙DMF (8∙DMF; 2Me4Claza = 2-methyl-4-chloro-7-azaindole). Complexes showed high in vitro cytotoxicity against nine human cancer cell lines (IC50 ranging from 0.4 to 12.8 μM), including the cisplatin-resistant ovarian cancer cell line (A2780R; IC50 = 1.0–3.5 μM). The results of in vivo testing, using the L1210 lymphocytic leukaemia model, at the equimolar doses of Pt with cisplatin (2 mg/kg) confirmed the activity of complex 8 comparable to cisplatin. From the mechanistic point of view, evaluated ex vivo by Western blot analyses on the samples of isolated tumour tissues, the treatment of the animals with complex 8, contrary to cisplatin, decreased the levels of tumour suppressor p53 and increased significantly the amount of intracellular anti-apoptotic protein MCL-1L (37 kDa). Additionally, the active form of caspase 3 was significantly elevated in the sample of tumour tissues treated with complex 8, indicating that the activation of p53-independent cell-death pathway was initiated. The light and electron microscopy observations of the cancerous tissues revealed necrosis as a dominant mechanism of cell death, followed by scarce signs of apoptosis. The additional results (e.g. in vitro interaction experiments with selected biomolecules, cell cycle perturbations, gel electrophoretic studies on pUC19 plasmid DNA) supported the hypothesis that the complexes might be involved in the mechanism of action quite different from cisplatin.